2012
DOI: 10.1007/s12031-012-9786-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by L-Type Calcium Channels of Endocytosis: An Overview

Abstract: The exocytotic neurotransmitter release process is tightly coupled to the membrane retrieval (endocytosis) process since both are calcium-dependent processes. For instance, at the adrenal chromaffin cells, catecholamine release is regulated by Ca(2+) entry through L, N and PQ subtypes of voltage-dependent calcium channels (VDCC). The contribution of a given VDCC subtype to exocytosis may differ according to the animal species studied, with L channels contributing only about 20 % to the total Ca(2+) entry in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Altogether, our results suggest that L-type CCBs may enhance the cellular internalization of cp-asiRNAs. These results correlated with previous findings suggesting that the inactive state of the L-type calcium channel stimulates endocytosis by sustaining membrane depolarizations for a longer time. , …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Altogether, our results suggest that L-type CCBs may enhance the cellular internalization of cp-asiRNAs. These results correlated with previous findings suggesting that the inactive state of the L-type calcium channel stimulates endocytosis by sustaining membrane depolarizations for a longer time. , …”
Section: Resultssupporting
confidence: 92%
“…In contrast, the T-type calcium channel blockers, penfluridol and ethosuximide, failed to enhance the cp-asiRNA activity, possibly due to the absence of key features associated with L-type CCBs. Consistent with this idea, it has been reported that DHP L-type calcium channel antagonists stabilize and inactivate L-type calcium channels and the slow inactivation of the persistent and lasting (L-type) calcium channel was related to endocytosis. , …”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The DSC1 channel could take part in the regulation of synaptic vesicle cycling, which is critical for synaptic transmission [24]. Both exocytotic release and re-uptake by endocytosis are controlled by Ca 2+ influx [24], [25]. Interestingly, the identity of the calcium channel that controls endocytosis at the presynaptic terminals has not been identified in insects, raising the intriguing possibility that the DSC1/BSC1 channel could be a candidate.…”
Section: Discussionmentioning
confidence: 99%